Identification of CalDAG-GEFI as an intracellular target for the vicinal dithiol binding agent phenylarsine oxide in human platelets - Kuo, Chih-Yun; Wang, Hui-Chun; Kung, Po-Hsiung; Lu, Chi-Yu; Liao, Chieh-Yu; Wu, Ming-Tsang; Wu, Chin-Chung (Thrombosis and Haemostasis, 2014)
CalDAG-GEFI, a guanine nucleotide exchange factor activating Rap1, is known to play a key role in Ca2+-dependent glycoprotein (GP)IIb/IIIa activation and platelet aggregation. Although inhibition of CalDAG-GEFI could be a potential strategy for antiplatelet therapy, no inhibitor of this protein has been identified. In the present study, phenylarsine oxide (PAO), a vicinal dithiol blocker, potently prevented Rap1 activation in thrombin-stimulated human platelets without significantly inhibiting intracellular Ca2+ mobilisation and protein kinase C activation. PAO also prevented the Ca2+ ionophore-induced Rap1 activation and platelet aggregation, which are dependent on CalDAG-GEFI. In the biotin-streptavidin pull-down assay, CalDAG-GEFI was efficiently pull-downed by streptavidin beads from the lysates of biotin-conjugated PAO-treated platelets, suggesting that PAO binds to intracellular CalDAG-GEFI with high affinity. The above effects of PAO were reversed by a vicinal dithiol compound 2,3-dimercaptopropanol. In addition, CalDAG-GEFI formed disulfide-linked oligomers in platelets treated with the thiol-oxidant diamide, indicating that CalDAG-GEFI contains redox-sensitive thiols. In a purified recombinant protein system, PAO directly inhibited CalDAG-GEFI-stimulated GTP binding to Rap1. Using CalDAG-GEFI and Rap1-overexpressed human embryonic kidney 293T cells, we further confirmed that PAO abolished Ca2+-mediated Rap1 activation. Taken together, these results have demonstrated that CalDAG-GEFI is one of the targets of action of PAO, and propose an important role of vicinal cysteines for the functions of CalDAG-GEFI.
Keywords: CalDAG-GEFI; Rap1; platelet aggregation; phenylarsine oxide; vicinal dithiol